A possible mechanism of failure in dynamic uniaxial compression and the size effect. (November 2021) - Dyskin, Arcady V.; Pasternak, Elena; Qi, Chengzhi; Xia, Chen; Qu, Xiaolei
Highlights: We propose a new concept of failure under the split Hopkinson pressure bar. Circumferential dynamic stress ensures extensive crack propagation in uniaxial compression. Size effect in dynamic loading is based on the action of radial component of dynamic stress. Abstract: It is known from the split Hopkinson pressure bars experiments on dynamic uniaxial compression of brittle materials such as rocks and concrete that the strength increases with the increase of loading rate and the sample size. Friction and crack propagation do depend upon the loading rate, but this dependence would lead to the opposite effect – the strength decrease with the loading rate. Forrestal et al. (2007) showed that in dynamic loading the inertia effect induces additional, dynamic stresses. We demonstrate that (1) the circumferential component of the dynamic stress works to enable the failure mechanism based on extensive crack growth in uniaxial compression sufficient to cause splitting or spallation; (2) the radial component increases the strength by reducing the extent of wing crack growth such that higher load is required to induce failure. We propose a model of brittle dynamic failure which predicts the observed increase in dynamic compressive strength with the loading rate and sample size.